The Commercial Advertising Frequency on Television and the Role of Food Vlogger towards Economic Improvement during the Covid-19 Pandemic in Northern Bekasi - Andrian; Haryudi; Ria Lestari Pangastuti (East Asian Journal of Multidisciplinary Research, 2022)
The research aims to know whether the small and middle business can struggle against the situation of Covid-19 pandemic in Northern Bekasi nowadays.  The research methodology used was descriptive quantitative and multiple linear regression analysis, and analyzed by SPSS version 22, covered Validity, Reliability, Normality, Multicolinierity, Heteroscedasticity, Hyphotesis, and Coefficient Determination Test. The results of this study are that Commercial Advertising Frequency on Television variable has a negative and no significant effect on Economic Improvement while the Role of Food Vlogger variable has a positive and significant effect on Economic Improvement. The uniqueness of this study is that Economic Improvement variable can be more affected by the Role of Food Vlogger variable of  4.7% than the other factors.